2019
DOI: 10.1111/dth.13094
|View full text |Cite
|
Sign up to set email alerts
|

Immediate post‐irradiation dermoscopic vascular changes versus purpura as a therapeutic endpoint in pulsed‐dye laser treatment of port wine stains

Abstract: Pulsed‐dye laser (PDL) is the treatment of choice for port wine stain (PWS), and the development of purpura is considered a therapeutic endpoint. Changes in PWS vasculature observed by dermoscopy immediately after laser irradiation have been suggested to predict the minimal effective fluence. The current study aimed at comparing these changes with purpura as a therapeutic endpoint. Fifty‐six PWS patients, randomized into two groups, received five monthly PDL sessions (595 nm and 10 mm spot size). At the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Five studies (5.9%) were placebo-controlled. Thirty-two percent (N = 28/85) of studies was randomized (i.e., randomization of treatments to different patients or to different sites within one patient and/or PWS) [ 11 , 31 , 36 , 39 , 41 59 , 61 , 62 , 81 , 92 , 103 ]. Of the uncontrolled (noncomparative) studies (N = 42/75 [ 63 69 , 71 80 , 82 91 , 93 102 , 104 108 ]), 11 were performed to correlate, develop, or validate an instrument or analysis technique (such as laser speckle imaging; intended for measuring lesion characteristics, treatment effects, or efficacy), 1 study investigated different clinical assessment methods, and 1 study correlated PWS characteristics and demographic parameters with treatment results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (5.9%) were placebo-controlled. Thirty-two percent (N = 28/85) of studies was randomized (i.e., randomization of treatments to different patients or to different sites within one patient and/or PWS) [ 11 , 31 , 36 , 39 , 41 59 , 61 , 62 , 81 , 92 , 103 ]. Of the uncontrolled (noncomparative) studies (N = 42/75 [ 63 69 , 71 80 , 82 91 , 93 102 , 104 108 ]), 11 were performed to correlate, develop, or validate an instrument or analysis technique (such as laser speckle imaging; intended for measuring lesion characteristics, treatment effects, or efficacy), 1 study investigated different clinical assessment methods, and 1 study correlated PWS characteristics and demographic parameters with treatment results.…”
Section: Resultsmentioning
confidence: 99%
“…of studies was randomized (i.e., randomization of treatments to different patients or to different sites within one patient and/or PWS) [11,31,36,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]61,62,81,92,103]. Of the uncontrolled (noncomparative) studies (N = 42/75 [63][64][65][66][67][68][69][71][72][73][74][75][76][77][78][79][80][82][83][84][85][86][87]…”
Section: Plos Onementioning
confidence: 99%
“…Another study found that the immediately dermoscopy performance after HMME-PDT, which showed vascular rupture, punctate or globular hemorrhage shadow, indicating a better later efficacy. 25 , 26 That may be a predictive marker of efficacy.…”
Section: Effect Evaluationmentioning
confidence: 99%
“…Immediate disappearance of vessels in the treated field was comparable to purpura as an end point in treatment of PWS with PDL. This may avoid the usage of higher fluences to obtain purpuric end point and is cosmetically more acceptable than a purpura as it takes up to 2 weeks to fade 19 …”
Section: Epiluminescence Microscopy or Dermoscopymentioning
confidence: 99%